DIPETALONEMIASIS IN A DROMEDARY CAMEL AND ITS TREATMENT - S. A. Muhammad, A. A. Farooq, M. S. Akhtar and C. S. Hayat1 (Pakistan Veterinary Journal, 2004)
A 16 years old female camel was presented for treatment of dipetalonemiasis at the outdoor clinic of the Department of Clinical Sciences, Gomal College of Veterinary Sciences, Gomal University, Dera Ismail Khan. The animal was emaciated and was showing dysnea. The mucus membranes of eye and oral cavity were pale yellow and pharyngeal lumph node was swollen. Examination of blood revealed eosinophilia with a marked decrease in haemoglobin level. The camel was positive for haemoparasite Dipetalonema evansia and recovered following treatment with Ivermectin.